Cardiac dysfunction associated with a nucleotide polymerase inhibitor for treatment of hepatitis C. Issue 2 (26th May 2015) - Ahmad, Tariq; Yin, Philip; Saffitz, Jeffrey; Pockros, Paul J.; Lalezari, Jacob; Shiffman, Mitchell; Freilich, Bradley; Zamparo, Joann; Brown, Kyle; Dimitrova, Dessislava; Kumar, Monica; Manion, Doug; et al.
<x xml:space="preserve">Abstract</x> Treatment for chronic hepatitis C virus (HCV) infection is evolving from interferon (IFN)‐based therapy to direct‐acting antiviral (DAA) agents, yet some safety concerns have arisen involving cardiac toxicity. In this study, we sought to better understand the potential off‐target toxicities of new DAAs. We retrospectively evaluated the clinical and pathological findings of the sentinel case in a phase II study that led to clinical development discontinuation for BMS‐986094, an HCV nucleotide polymerase (nonstructural 5B) inhibitor. We also report on outcomes from other patients in the same study, including electrocardiogram changes, cardiovascular biomarkers, and transthoracic echocardiograms. Thirty‐four patients received IFN‐free BMS‐986094 regimens. Six patients had left ventricular ejection fractions (LVEFs) <30%, 8 had LVEFs 30%‐50%, and 11 required hospitalization for suspected cardiotoxicity. Of the patients with LVEF <50%, 6 had normalization of systolic function after a median of 20 days. T‐wave inversions were the most sensitive predictor of LVEF dysfunction. B‐type natriuretic peptide levels increased over time and correlated with the degree of LVEF dysfunction. Pathological analysis of cardiac tissue revealed severe myocyte damage with elongated myofibrils without gross necrosis. These findings were consistent with some results of recent primate studies that were conducted to further investigate the potential mechanisms of BMS‐986094 toxicity. Conclusion: A novel nucleotide analog polymerase inhibitor developed for HCV treatment may cause a toxic cardiomyopathy. Ongoing surveillance of DAAs for cardiotoxicities may be beneficial, especially among patients at higher risk for cardiovascular disease. (Hepatology 2015;62:409–416